Pudeur, place, and print: modesty, agency, and collaboration in sixteenth-century French women’s writing - Patel, N (2021)
This thesis considers responses to modesty in the works of four sixteenth-century French women writers who work with and reclaim modesty in different ways. I focus on Marguerite de Navarre, the Dames des Roches, and Gabrielle de Coignard who span the sixteenth century and operate in different locations: Nérac, Poitiers, and Toulouse. Firstly, I examine how far their works reflect discourses of modesty in circulation, and whether these responses are shaped by the locations, physical and thematic, in which they live. Occasionally tracking (im)pudeur and cognate terms, this exploration mainly offers textual commentaries on these key terms: virginity, chastity, desire, sex, the female body, nudity, shame, and silence. I document how the importance of modesty changes over time and the shifts or movement between locations in the production and circulation of texts, from salon-type structures to printed works. The process becomes more complex when considering common associations between print and sexual deviance which compromised a woman’s modesty. A second aspect of this thesis explores a creative response to this nexus, which I term ‘collaborative modesty’: networks of male and female collaborators that influence the composition, publication, and reception of women writers’ texts. Alongside the intervention of male figures, a striking mother-daughter relationship emerges; daughters play a vital role in how their mothers are received in print, contemporarily and retrospectively. This thesis reconsiders understandings of early modern French women writers as ‘submissive’ or ‘subversive’, by focusing on the agency that they achieve within the confines of society. Secondly, it offers a new concept of collaboration which dispels the myth of ‘male genius’ that for too long defined understandings of authorship. Literary collaboration is translocational and transactional; it does not simply consist of poets and writers. ‘Modest’ figures such as daughters, printers, and editors, all play an important role in literary creation.